Fatty acid based biocarbonates: Al-mediated stereoselective preparation of mono-, di- and tricarbonates under mild and solvent-less conditions. Issue 15 (7th June 2017) - Peña Carrodeguas, L.; Cristòfol, À.; Fraile, J. M.; Mayoral, J. A.; Dorado, V.; Herrerías, C. I.; Kleij, A. W.
Abstract : Various epoxidised fatty acids are conveniently converted into biocarbonates under mild and solvent-less conditions with unprecedented high levels of diastereoselectivity. Abstract : A catalytic method for the preparation of a series of fatty acid derived biocarbonates has been developed using a binary Al-complex/PPNCl catalyst. This catalyst system allows conversion of fatty acid derived epoxides under comparatively mild reaction conditions (70–85 °C, 10 bar) while maintaining high levels of diastereospecificity with cis / trans ratios of up to 97 : 3 in the products. The comparative catalysis data obtained for the reactions catalysed only by the nucleophilic halide based components show that the presence of the Al-complex is crucial for the retention of the original stereochemistry.